2004
DOI: 10.1111/j.1365-263x.2004.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience in children with congenital heart disease: a case‐control study

Abstract: Swedish children with complex congenital heart disease have poorer dental health than healthy age and gender matched controls in spite of intensive preventive efforts. In many cases, intervention had been given when caries were present. A closer cooperation between paediatric cardiology and paediatric dentistry is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 9 publications
8
99
3
4
Order By: Relevance
“…2,4,5,7,19 A high caries index was found in the present study, in contrast with recent data on the whole Brazilian population, in which a mean dmft value of 2.43 was found for a 5-year-old population in which 46.6% were caries free. 20 This may be related to the high complexity of congenital cardiac disease and the greater health demands made by this medical condition.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…2,4,5,7,19 A high caries index was found in the present study, in contrast with recent data on the whole Brazilian population, in which a mean dmft value of 2.43 was found for a 5-year-old population in which 46.6% were caries free. 20 This may be related to the high complexity of congenital cardiac disease and the greater health demands made by this medical condition.…”
Section: Discussioncontrasting
confidence: 55%
“…2,5 The use of sucrose as a sweetening agent in liquid medicines, particularly in pediatric practice, could explain this finding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These conditions are not currently recognized as one of the most common noncardiac inpatient needs for this population, although a few previous studies [15][16][17][18] have reported worse dental caries experience and comorbidities in digestive system for children with heart disease. However, it is unclear from this study whether these admissions simply reflect more inpatient needs for this population on commonly seen conditions due to anesthesia concerns or that these children indeed had worse dental and digestive outcomes.…”
mentioning
confidence: 99%
“…Neuropsychiatric conditions such as ADHD and autism have been shown to influence caries prevalence in groups of children with these diagnosis (Chandra, Anandakrishna et al 2009, Blomqvist, Ahadi et al 2011, El Khatib, El Tekeya et al 2014 and HRQoL (Danckaerts, Sonuga-Barke et al 2010, Kuhlthau, Orlich et al 2010, Domellöf, Hedlund et al 2014, Lee, Yang et al 2016, Peasgood, Bhardwaj et al 2016. Also asthma, congenital heart disease and diabetes can increase caries risk (Ponte, Tabaj et al 2001, Stecksén-Blicks, Rydberg et al 2004, Alavaikko, Jaakkola et al 2011, Johnston and Vieira 2014, Sivertsen, Assmus et al 2016) and impair HRQoL (Varni, Limbers et al 2007, Chaplin, Hanas et al 2009, Hanberger, Ludvigsson et al 2009). Although the proportion of affected children was slightly higher in children with CL/P than in the non-cleft controls this alone could not explain the difference in caries prevalence and frequency in 5-year-old children, or the differences in caries risk.…”
Section: Methodological Considerations Participantsmentioning
confidence: 99%